The Development of a Tutorial Video on Cognitive Behavior Modification for School Counselors to Address Anxiety Cases - Deni Wijaya; Farida Aryani; Abdullah Pandang; Sulaiman Samad (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to describe (1) the needs of the tutorial video on Cognitive Behavior Modification (CBM) counseling for the school counselors in Makassar to address student anxiety, (2) the prototype of the CBM tutorial video for the school counselors inMakassar to address student anxiety, and (3) the validity of the CBM tutorial video for the school counselors in Makassar to address student anxiety. This study adopted a research and development design by Borg & Gall (2003). Questionnaires, interviews and scale were used to collect data. The results of the study revealed that (1) the tutorial video on Cognitive Behavior Modification (CBM) counseling was needed by the school counselors in Makassar to address student anxiety, (2) the video consisted of two parts: an overview of the CBM approach and the steps of CBM counseling, and (3) the tutorial video on Cognitive Behavior Modification (CBM) counseling for the school counselors in Makassar to address student anxiety was found to be valid to use.